2011
DOI: 10.1039/c0cp01830a
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency electronic and optical properties of rhombohedral graphite

Abstract: Low-energy electronic and optical properties of ABC-stacked graphite are respectively studied by the tight-binding model and gradient approximation. The band structures include linear and parabolic bands with and without degeneracy. They show strongly anisotropic dispersions. ABC-stacked graphite is a semimetal due to the slight overlap near the Fermi level between the conduction and valence bands. The interlayer interactions change the energy dispersion, state degeneracy, and the positions of band-crossings a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…As compared to the bulk bands of rhombohedral graphite with DFT 7,[23][24][25] and tight binding 25 calculations, and to the evolution of graphene to graphite with tight binding calculation 19 , it is clear that these states are surface states of the few-layer rhombohedral graphene. In order to understand the amount of charge needed to fill the flat surface band and close the gap, we have integrated first peak of the density of states above the gap.…”
Section: Appendix C: Metallic and Paramagnetic Bandsmentioning
confidence: 99%
“…As compared to the bulk bands of rhombohedral graphite with DFT 7,[23][24][25] and tight binding 25 calculations, and to the evolution of graphene to graphite with tight binding calculation 19 , it is clear that these states are surface states of the few-layer rhombohedral graphene. In order to understand the amount of charge needed to fill the flat surface band and close the gap, we have integrated first peak of the density of states above the gap.…”
Section: Appendix C: Metallic and Paramagnetic Bandsmentioning
confidence: 99%
“…As a matter of fact, in graphite, it has been known that the interlayer hybridization at special points of the BZ is much affected by the stacking pattern [20][21][22][23]. By carefully examining electronic band structures in the literature, one can find the quasi-two-dimensional states due to this effect in a variety of works not only on graphite [20][21][22][23][24][25][26][27][28][29][30][31]. In addition, it has recently been experimentally demonstrated that this interference can be utilized for controlling the interlayer motion of electrons and holes by the stacking geometry [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…The consistency of two methods is very useful in the further studies on the other essential properties, e.g. the optical [63], magnetic [64] and transport properties [65] of guest-atom-substituted silicenes/germaneness.…”
Section: Spatial Distribution Of Charge Densitymentioning
confidence: 99%